THE THE INFLUENCE OF THE READING TO LEARN LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES OFF VII GRADE STUDENTS - Lani Dian Orchida; Rani Oktavia (Pendidikan IPA, FMIPA, UNP, 2025)
One of the key indicators of students’ scientific understanding and skills is their learning outcomes. Based on interviews with science teachers at SMPN 7 Padang, it was found that students’ learning outcomes remain low due to limited motivation, low interest in learning science, and suboptimal learning readiness. To address this issue, the Reading to Learn (R2L) model was applied as an alternative learning strategy to improve student achievement. This study aimed to examine the effect of implementing the Reading to Learn model on students’ learning outcomes. The research sample consisted of class VII.5 as the experimental group and class VII.6 as the control group, each comprising 33 students. The results revealed a significant difference between the two groups: the experimental group achieved an average score of 81, while the control group scored an average of 56. The t-test analysis yielded a t-value of 5.948, exceeding the t-table value of 1.997 (tcount > ttable = 5.948 > 1.997). Therefore, H₀ was rejected and H₁ was accepted, indicating that the implementation of the Reading to Learn model had a significant positive effect on students’ learning outcomes.